DAMPAK DAMPAK PERBEDAAN POLA ASUH DAN POLA DIDIK ORANG TUA DENGAN MEMBEDA-BEDAKAN ANAK (SIBLING DISCRIMINATION) - Rizka Ayu Abdella; Mutimmatul Faidah (LPPM Universitas Negeri Surabaya, 2026)
Differential Parental Treatment (DPT) refers to variations in how parents treat their children, a common family dynamic that can significantly influence children’s psychosocial development and the quality of sibling relationships. In Indonesian families, this phenomenon is shaped by cultural influences such as age hierarchy, gender roles, and family norms, which affect how parents distribute attention, discipline, and educational support. Using a quantitative correlational design, this study examined the extent of DPT and its associations with children’s self-esteem, anxiety levels, academic learning, and sibling relationships among 30 families in Malang. The results show that many children perceived moderate to high levels of unequal treatment, which were linked to increased sibling conflict and higher anxiety. Additionally, discrepancies were found between children’s and parents’ perceptions, particularly regarding the intensity of differential treatment and sibling conflict, highlighting the importance of fair, consistent, and communicative parenting practices to promote healthier sibling relationships and support children’s psychosocial well-being. Keywords : differential parental treatment, parenting, child psychosocial development, sibling conflict